Understanding vibropeening - Lee, Ze Xin. (2010)
Vibropeening is a process combining vibratory polishing and shot peening from a single polishing process in a vibratory bowl. The project looks into quantifying and analysing the stress distributions occurring in a flat titanium 6Al-4V work piece during vibratory polishing with round steel medias. The peening effect induced by the steel media is then verified against an actual experiment done by Boeing with similar parameters. The project demonstrated how FEA modelling could be used to better define compressive stress levels occurring in a 2D work piece during vibratory peening. The model was subjected to a time-based bombardment of media onto work piece surface. The vibration was induced by defining a displacement based response to a bowl structure, followed by transferring of energy to media, and finally from media to work piece. The end results were compared against stress patterns displayed in Boeing’s research paper “Evaluation of Vibrostrengthening for Fatigue Enhancement of Titanium Structural Components on Commercial Aircraft” where an actual vibropeening experiment was carried out, and showed that the stress trends on the FEA model coincided with Boeing’s experiment, hence verifying the usage of FEA on vibropeening.